2017
DOI: 10.1128/iai.00189-17
|View full text |Cite
|
Sign up to set email alerts
|

Aeromonas salmonicida Growth in Response to Atlantic Salmon Mucins Differs between Epithelial Sites, Is Governed by Sialylated and N -Acetylhexosamine-Containing O -Glycans, and Is Affected by Ca 2+

Abstract: Aeromonas salmonicida causes furunculosis in salmonids and is a threat to Atlantic salmon aquaculture. The epithelial surfaces that the pathogen colonizes are covered by a mucus layer predominantly comprised of secreted mucins. By using mass spectrometry to identify mucin glycan structures with and without enzymatic removal of glycan residues, coupled to measurements of bacterial growth, we show here that the complex Atlantic salmon intestinal mucin glycans enhance A. salmonicida growth, whereas the more simpl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 45 publications
1
37
0
Order By: Relevance
“…Instead, we observed a positive correlation between growth and the abundance of acidic and fucosylated structures and a negative correlation with the abundance of galactose terminating structures on the mucins, and culture with fucose and galactose monosaccharides supported these effects. We have previously cultured another bacteria (Aeromonas salmonicida) with twice as high concentration of galactose without inhibition of growth, 21 suggesting that the inhibition of growth seen in the current study is not affecting all bacteria. Each mucin carried 35-75 glycans, and the growth response to the mucins is thus likely to be the sum of multiple glycans.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Instead, we observed a positive correlation between growth and the abundance of acidic and fucosylated structures and a negative correlation with the abundance of galactose terminating structures on the mucins, and culture with fucose and galactose monosaccharides supported these effects. We have previously cultured another bacteria (Aeromonas salmonicida) with twice as high concentration of galactose without inhibition of growth, 21 suggesting that the inhibition of growth seen in the current study is not affecting all bacteria. Each mucin carried 35-75 glycans, and the growth response to the mucins is thus likely to be the sum of multiple glycans.…”
Section: Discussionmentioning
confidence: 58%
“…18 The high diversity of mucin O-glycans provides an extensive repertoire of bacterial attachment sites and O-glycans take part in host-pathogen interactions in the gastrointestinal tract. [19][20][21][22] Mucus can be beneficial for bacteria by providing nutrients for growth 23,24 and protecting bacteria from the harmful environment. 25 Mucins can also prevent close contact of the pathogen with the gastric epithelial cells by binding, which may contribute to removing the bacteria from their niche with the gastric emptying.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty-five microliters of colonic mucins from five B. hyodysenteriae-infected pigs and six healthy pigs (2) and the carbohydrates galactose, fucose, NeuAc, NeuGc, GlcNAc, and GalNAc (Sigma-Aldrich, St. Louis, MO, USA) diluted in PBS (100 g/ml) were added to a sterile Falcon 96-well plate (Corning Life Sciences, Corning, NY, USA). B. hyodysenteriae was harvested from the agar plates, washed in PBS, and resuspended in carbohydrate-free medium (40) to an optical density at 600 nm (OD 600 ) of 0.1. RealTime-Glo cell viability assay reagent (Promega, Madison, WI, USA) was diluted 1/1,000 in the bacterial suspension, and 225 l of the bacterial suspension with the reagent was added per well.…”
Section: Methodsmentioning
confidence: 99%
“…Although specific molecules responsible for this activity have not yet been identified, O'toole et al [126] suggested that free amino acids and carbohydrates could act as chemoattractant molecules in trout mucus (skin and intestinal) while Klesius et al [127] suggested that a lectin-like substance might be responsible for bacterial chemotaxis in catfish (Ictalurus punctatus). In recent studies, Padra and colleagues found that fish mucosal sialic acids and specifically N-acetylglucosamine (GlcNac) play an important role in the pathogenic bacteria Aeromonas salmonicida growth and binding to its host [152,153].…”
Section: Interspecific Communicationmentioning
confidence: 99%